Comparison of algorithms for fetal signal reconstruction: Projector Operator vs. Independent Component Analysis - Comani, S; Preissl, H; Mantini, D; Campbell, Q; Alleva, G; Eswaran, H (2007)
The aim of this work was to compare the performances of the Projector Operator (PO) and the independent component analysis (ICA) based method for fetal signal extraction from fMCG. Both methods were applied on data recorded with the SARA system installed at the UAMS, Little Rock (Arkansas-USA), and with the ATB system installed at ITAB-Chieti (Italy). Twenty datasets recorded with both systems were analysed. The detection rates, signal-to-noise ratios, fetal signal amplitude reconstructions and residual maternal contamination of the reconstructed fetal signals were calculated, and the PO and ICA-based approach provided fetal signals with similar features, although ICA seemed to be more effective when noisy data were processed. © 2007 Elsevier B.V. All rights reserved.